GnRH replacement rescues cognition in Down Syndrome - Manfredi-Lozano, Maria (Science, 2022)
Currently, no viable treatment exists for cognitive and olfactory deficits in Down syndrome (DS). We show in a DS model (Ts65Dn mice) that these progressive non-reproductive neurological symptoms closely parallel a post-pubertal decrease in hypothalamic as well as extra-hypothalamic expression of a master molecule controlling reproduction – gonadotropin-releasing hormone (GnRH), and appear related to an imbalance in a microRNA-gene network known to regulate GnRH neuron maturation together with altered hippocampal synaptic transmission. Epigenetic, cellular, chemogenetic and pharmacological interventions that restore physiological GnRH levels abolish olfactory and cognitive defects in Ts65Dn mice, while pulsatile GnRH therapy improves cognition and brain connectivity in adult DS patients. GnRH thus plays a crucial role in olfaction and cognition, and pulsatile GnRH therapy holds promise to improve cognitive deficits in DS.